2013
DOI: 10.2139/ssrn.2294676
|View full text |Cite
|
Sign up to set email alerts
|

How Do the Changing Labor Supply Behavior and Marriage Patterns of Women Affect Social Security Replacement Rates?

Abstract: for their thoughtful comments and suggestions.© 2013, April Yanyuan Wu, Nadia S. Karamcheva, Alicia H. Munnell, and Patrick Purcell. All rights reserved. Short sections of text, not to exceed two paragraphs, may be quoted without explicit permission provided that full credit, including © notice, is given to the source. About the Center for Retirement ResearchThe Center for Retirement Research at Boston College, part of a consortium that includes parallel centers at the University of Michigan and the National B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…As women's labor force participation and earnings increase, more and more female retirees will receive benefits based on their own working record, and fewer of them will be eligible for only auxiliary benefits, based on their husbands' working history. Wu et al (2013) reported that only 37 percent of the 24 to 35 year-old women in the Depression Era 1 (1931)(1932)(1933)(1934)(1935) cohort worked, compared with 73 percent of their counterparts, born 35 years later -Gen X (1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975). The increase in the propensity to work is particularly pronounced among married women.…”
Section: Women's Changing Life and The Social Security Programmentioning
confidence: 99%
See 1 more Smart Citation
“…As women's labor force participation and earnings increase, more and more female retirees will receive benefits based on their own working record, and fewer of them will be eligible for only auxiliary benefits, based on their husbands' working history. Wu et al (2013) reported that only 37 percent of the 24 to 35 year-old women in the Depression Era 1 (1931)(1932)(1933)(1934)(1935) cohort worked, compared with 73 percent of their counterparts, born 35 years later -Gen X (1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973)(1974)(1975). The increase in the propensity to work is particularly pronounced among married women.…”
Section: Women's Changing Life and The Social Security Programmentioning
confidence: 99%
“…Compared to 30 years ago, married women today have higher levels of education, increased labor force participation, more stable career trajectories, and higher salaries. Wu et al (2013) examined how women's changing lives have affected the Social Security replacement rates that individuals and households receive at the time of first claiming. Their study found that Social Security replacement rates have dropped sharply at both the household and individual levels, and the declines will continue for future retirees.…”
Section: Introductionmentioning
confidence: 99%
“…But they can provide an important illustration of some of the longitudinal properties of high earnings and how they would play out under proposals to remove or increase OASDI's contribution and benefit base. 37 We would expect that future cohorts, and especially future cohorts of women, would have different experiences (see, for example, Wu et al 2013). …”
Section: Implications Of Earnings Patterns For Benefit Levels Under Cmentioning
confidence: 99%
“…This is particularly true of teachers, whose earnings increase quite significantly at the end of their careers, despite a lack of agreement amongst researchers about whether quality also increases over this period (Papay and Kraft 2015; Wiswall, 2013; Clotfelter et al 2006; Rivkin, Hanushek and Kain, 2005; and Rockoff, 2004). Also drawing attention to teacher pensions is the fact that some teacher pension benefits provide retirees with income replacement rates over 85 percent, making retirement benefits much more generous than, for example, the median Social Security benefit (Wu et al 2013). …”
Section: Introductionmentioning
confidence: 99%